STUDI TENTANG KERAJINAN SULAMAN BENANG EMAS DI NAGARI SANIANGBAKA KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - UTARI, AYU GUSTI; Zahri, Wildati; Idrus, Yenni (Journal of Home Economics and Tourism, 2014)
Gold thread embroidery craft is one of the craft in Saniangbaka villages that have economic value and beauty value which has been handed down and done by women. The purpose of this study was to describe the shape of motifs of gold thread embroidery, materials used for gold thread embroidered, techniques of gold thread embroidery, and types of gold thread embroidery products. This study uses qualitative method. The type of data is primary and secondary data. The technique of collecting data through observation, interview and documentation. The data analysis technique which uses interactive model analysis that is related with subject matter is data reduction model, data presentation, and conclusion. The results of the study are: Shape of gold thread embroidery motifs derived from the naturalistic form of plants and animals, such as florals, leaves, twigs, chicken, bird, and geometric such as triangles, rectangles, circles, from then on stylized motifs into decorative ornament. Materials used are velvet, satin, gold embroidery threads, sewing machine thread, and needles for hand embroidery. Gold thread embroidery techniques in Saningbaka villages use pamedangan legged, namely gold thread laid on the surface of the fabric and embroidered motif followed by way of regular sewing thread pinned gold thread, gold thread embroidery characteristic in this Saniangbaka villages its motive is always full with gold threads, is not only the edge of motive, called the Or nu'e techniques. Gold thread embroidery products in Saniangbaka villages produced is for custom fixtures and traditional wedding, while products such as wall hangings, clothing, tablecloths, pillowcases seats, and souvenirs in the form of purses, bags and toys key is a special order from the buyer , is expected to yield gold thread embroidery is to improve the economy and can be preserved.